Pró-dieta: gerador automático de cardápios personalizados baseado em algoritmos genéticos - Gomes, Frederico Renato (2012)
The use of computer systems and artificial intelligence techniques to solve real world problems are increasingly common. In the nutrition area it is not different and, in Brazil and worldwide, systems are found to aid the prescription of food menus and diet formulation. The purpose of this paper is to present a methodology for prescription food menus and diet formulation, prioritizing the principles of healthy eating, emphasizing the variety of colors, combination of flavors, texture balance, the breaking of monotony and food supplying of all nutrients, besides contributing to the disciplines of Computer Science applied to Nutrition of the Federal Institute of Triangle Mineiro. To analyze this methodology, it was created a computer system using Genetic Algorithms to find satisfactory solutions in an acceptable time on a wide table food prepared in portion sizes. The experimental results were satisfactory, proving the effectiveness of the methodology.